2022
DOI: 10.3390/pathogens11030358
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Salmonella enterica Contamination in Pork and Poultry Meat from São Paulo/Brazil: Serotypes, Genotypes and Antimicrobial Resistance Profiles

Abstract: Salmonellosis is a zoonosis of major relevance to global public health. Here we present the assessment of Salmonella enterica contamination in pork and poultry meat sold at retail markets in São Paulo, Brazil. A total of 780 meat samples (386 poultry meat and 394 pork samples) were collected from 132 markets. From these, 57 samples (7.3%) were positive for S. enterica isolation, including 32 (8.3%) poultry meat and 25 (6.3%) pork samples. S. enterica isolates were further characterized for serotyping, antimicr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 34 publications
0
6
0
1
Order By: Relevance
“…In the period from 2009 to 2018, the CDC reported 1,410 food-related salmonella outbreaks, of which 5.5% were associated with the consumption of pork (CDC, 2023). Gomes et al (2022) analyzed 780 samples of poultry and pork meat from Brazil, where 57 samples (7.3%) were identified as contaminated by salmonella. These contaminated samples were collected in 35 markets, of which 57.1% were classified as neighborhood butchers, 25.7% as supermarkets, 11.4% as municipal markets, and 5.7% as hypermarkets.…”
Section: Resultsmentioning
confidence: 99%
“…In the period from 2009 to 2018, the CDC reported 1,410 food-related salmonella outbreaks, of which 5.5% were associated with the consumption of pork (CDC, 2023). Gomes et al (2022) analyzed 780 samples of poultry and pork meat from Brazil, where 57 samples (7.3%) were identified as contaminated by salmonella. These contaminated samples were collected in 35 markets, of which 57.1% were classified as neighborhood butchers, 25.7% as supermarkets, 11.4% as municipal markets, and 5.7% as hypermarkets.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, an MDR profile has been common in most isolates [49,135,194,195,197]. In a temporal comparative analysis, it was demonstrated that 46.1% of S. Heidelberg isolates were resistant to only one class of antimicrobials in 2005, while 100% of them were MDR in 2009 [199]. Brazilian S. Heidelberg isolates have demonstrated a high frequency of resistance (>50%) to streptomycin, nalidixic acid, tetracycline, cefotaxime, ampicillin, amoxicillin, cefoxitin, amoxicillin-clavulanate, and ceftiofur [197].…”
Section: Salmonella Heidelbergmentioning
confidence: 99%
“…The Salmonella enterica serovar Typhimurium (ST) has become the most common serovar in pig production worldwide [ 3 ], including in Europe, the United States, and Brazil [ 4 , 5 , 6 ]. Additionally, ST has been recognized as a foodborne disease in humans, as contaminated pork is an considerable source of Salmonella infections in humans [ 7 ].…”
Section: Introductionmentioning
confidence: 99%